2013
DOI: 10.7553/68-2-742
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic journals for the dissemination of scholarly information by the University of Natal and the University of Zululand

Abstract: The study investigates the use of electronic journals for the dissemination of scholarly information in the Universities of Natal and Zululand. It attempts to determine the level of use of electronic journals by the scholarly communities, and the perceived impact that these journals have on the community. Similarly, the role played by the academic libraries in the provision of these journals was explored. The scholarly community included the academic staff, the library staff and postgraduate students. A survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The citation behaviour of the MIS students during the period under study was consistent with the conclusions of Mgobozi and Ocholla (2002) and Smith and Oppenheim (2001). Smith and Oppenheim (200 I) observed a continued dependence on monographs in assignments for the year 2000 when 40% of all citations were to book formats.…”
Section: Miscellaneous Government Docllll1entssupporting
confidence: 86%
See 2 more Smart Citations
“…The citation behaviour of the MIS students during the period under study was consistent with the conclusions of Mgobozi and Ocholla (2002) and Smith and Oppenheim (2001). Smith and Oppenheim (200 I) observed a continued dependence on monographs in assignments for the year 2000 when 40% of all citations were to book formats.…”
Section: Miscellaneous Government Docllll1entssupporting
confidence: 86%
“…Journal use for 2000 was only 29.5% of all citations. On the other hand, Mgobozi and Ocholla (2002) noted the low use of electronic journals by academics, librarians and postgraduates of the universities of Natal and Zululand. The findings were different to the studies by Friedlander (2002), Islam and Panda (2007), and Tenopir and Ennis (2002) which established a preference for consulting Internet resources by researchers as opposed to printed sources in answering reference queries.…”
Section: Miscellaneous Government Docllll1entsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nicholas, Williams, Rowlands, and Jamali (2010), electronic resources have made a tremendous impact on the research productivity of scholars in the United Kingdom, a view common in developed countries. In Africa, Mgobozi and Ocholla (2002) conducted a comparative study to investigate the relationship between the use of electronic journals by academic staff at the University of Natal and the University of Zululand in South Africa and their research productivity. According to the study, about 29% indicated a correlation whereas 13% indicated no correlation and others were undecided.…”
Section: Benefits Of Accessibility and Utilization Of Internet Resourcesmentioning
confidence: 99%
“…Ten (41.7%) pointed to the unavailability of computers with Internet facilities. Inadequate provision of computers with Internet facilities and the slow speed of computers were identified by past research as the reasons why students in an African academic environment were not using the Internet effectively (Ehikhamenor, 2003;Luambano and Nawe, 2004;Mgobozi and Ocholla, 2002;Mishra, Yadav and Kamini, 2005;Odero-Musakali and Mutula, 2007;Ojedokun, 200 I).…”
Section: Major Research Findings and Discussionmentioning
confidence: 99%